The Art of Landslides: How Stochastic Mass Wasting Shapes Topography and Influences Landscape Dynamics. Issue 8 (21st August 2022) - Campforts, Benjamin; Shobe, Charles M.; Overeem, Irina; Tucker, Gregory E.
Abstract: Bedrock landslides shape topography and mobilize large volumes of sediment. Yet, interactions between landslide‐produced sediment and fluvial systems that together govern large‐scale landscape evolution are not well understood. To explain morphological patterns observed in steep, landslide‐prone terrain, we explicitly model stochastic landsliding and associated sediment dynamics. The model accounts for several common landscape features such as slope frequency distributions, which include values in excess of regional stability limits, quasi‐planar hillslopes decorated with straight, closely spaced channel‐like features, and accumulation of sediment in valley networks rather than on hillslopes. Stochastic landsliding strongly affects the magnitude and timing of sediment supply to the fluvial system. We show that intermittent sediment supply is ultimately reflected in topography. At dynamic equilibrium, landslide‐derived sediment pulses generate persistent landscape dynamism through the formation and breaching of landslide dams and epigenetic gorges as landslides force shifts in channel positions. Our work highlights the importance of interactions between landslides and sediment dynamics that ultimately control landscape‐scale response to environmental change. Plain Language Summary: Landslides are natural hazards that predominantly occur where geologic forces have created steep, rugged terrain. Yet from a geologic perspective, landsliding is also one of the forces that contributes to shaping the landscape. Gaining insight into the role of landslides in shaping topography is critical to better understand the interplay between the factors driving long‐term landscape evolution, and ultimately controlling landslide hazard. Here, we use a computer simulation model to study how landslides help shape terrain. Simulating landslides enables us to identify the origins of several common features in mountainous topography. Model results illustrate how repeated landsliding can cause rivers and ridgelines to gradually but continually shift position over time, such that some mountain drainages grow while others shrink. This type of computer model, which describes how topography and landsliding influence one another, can help the scientific community understand the response of steep terrain to environmental changes, such as those related to climate and earthquakes. Key Points: Over geological timescales, landslides produce diagnostic topographic signatures that can be detected in real‐world topographic data Stochastic landsliding results in slopes exceeding stability angles and quasi‐planar hillslopes decorated with closely spaced channels The combination of landslide stochasticity and channel‐hillslope feedback mechanisms causes persistent landscape dynamism